CUSTOMER PERCEPTIONS ON THE ROLE OF BAITUL MAL WA TAMWIL, SUBANG CITY - Juhadi; Agus Koni; Fenny Damayanti Rusmana; Ridla Mutiah; Ade Albayan (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
The background of this research is that the financing provided by baitul mal wa tamwil has not been managed properly or by micro-entrepreneurs. Research related to customer perceptions of the role of baitul mal wa tamwil in Subang City uses quantitative research. The results of the study show that the financing of baitul mal wa tamwil is not significant to members' perceptions of business development and perceptions of increasing members' welfare. However, business development has a significant positive effect on the perception of increased member welfare. For micro business actors, it is hoped that they can make more use of the provision of financing to develop their business so that the role of financing becomes maximized. The conclusion of this study is that the effect of financing is not significant on business development and increasing welfare, so it is necessary to conduct similar research in other places with more subjects and objects.